Morphokinetics of embryos after IMSI versus ICSI in couples with sub‐optimal sperm quality: A time‐lapse study. (19th February 2021) - Boediono, Arief; Handayani, Nining; Sari, Henny Natalya; Yusup, Nuraeni; Indrasari, Wahyu; Polim, Arie A.; Sini, Ivan
Abstract: An investigation was conducted to determine the influence of two sperm selection modalities, IMSI and ICSI, on the morphokinetics, dynamic development and ploidy status of embryos derived from males with sub‐optimal sperm profiles during IVF program. A total of 209 PGTA‐tested top‐quality blastocysts (IMSI = 129, ICSI = 80) from 84 couples (IMSI = 51, ICSI = 33) were assessed retrospectively. This study found that both IMSI and ICSI yielded comparable embryo morphokinetics, except for the T7, TEB and CC3 parameters ( p  < 0.05). A significant lower incidence of multinucleation was observed in the IMSI group when compared to the ICSI group (48.8% vs. 71.3%, p  = 0.002), while other parameters of embryo development such as direct cleavage, distorted cytoplasmic movement, reverse cleavage and vacuole(s) appearance did not differ ( p  > 0.05). No differences were noticed in the proportion of generating chromosomally euploid embryos (44.2% vs. 51.3%, p  = 0.394, respectively, for IMSI and ICSI). The implementation of IMSI or ICSI in couples with sub‐optimal sperm profiles resulted in embryos with comparatively similar morphokinetics. Furthermore, the incidence of multinucleation at the two‐ to four‐cell stage was lower following the practice of IMSI, although the method did not improve the proportion of gaining euploid embryos.